Morbidity and mortality in the Cienfuegos Provincial Hospital (2018-2022) - Rodolfo Javier Rivero Morey; Lya del Rosario Magariño Abreus; Jeisy Rivero Morey; Arelys Falcón Hernández; Moisés Aramís Santos Peña (Medisur)
Background: morbidity and mortality are very sensitive health indicators; they show the populations’ reality, including the economic, cultural, and social spheres, by visualizing the death dimension in the population and its life quality. Objective: to determine the morbidity and mortality’s main causes in the Cienfuegos provincial hospital. Methods: descriptive and cross-sectional study, which included 151,670 patients treated at the Cienfuegos Dr. Gustavo Aldereguía Lima Provincial Hospital, in the clinical, surgical, emergency and maternal-infant specialties, from 2018 to 2022. Variables such as specialty, calendar year, hospital stay, and causes of morbidity and mortality were studied. A database was created for the statistical processing of information, obtained through the institution's statistical reports. Results: 48.7% of admissions corresponded to clinical specialties. The main morbidity causes were fever of unknown origin and spontaneous single birth, both with 7.5%. The 37.2% of the deceased had pneumonia as the cause of death. In 2021, 2,879 patients died; for a mortality rate of 8 per 1000 inhabitants. Conclusions: most patients who come to hospital services are admitted by clinical specialties with a stay. Fever of unknown origin and proximity to the end of the pregnancy are the main reasons for doctor's appointment; while pneumonic inflammatory processes and stroke are frequent causes of mortality, with a higher rate in intensive care units.